Liraglutide reduces hepatic glucolipotoxicity-induced liver cell apoptosis through NRF2 signaling in Zucker diabetic fatty rats - Guo, Jun (Mol Med Rep, 2018)
The primary aim of the present study was to evaluate the effects of liraglutide on glucolipotoxicity-induced liver cell apoptosis and the underlying mechanisms in Zucker diabetic fatty (ZDF) rats. The results revealed that liraglutide significantly decreased the body weight, hyperglycemia and hyperlipidemia of ZDF rats relative to those of Zucker lean (ZL) rats (P<0.05). Furthermore, the reduced liver cell apoptosis was observed in the ZDF rats following 6 weeks of liraglutide therapy. These data validated the beneficial effects of liraglutide on diabetic and obese ZDF rats. In addition, novel data was obtained that demonstrated that liraglutide treatment increased the expression of the antioxidant transcription factor nuclear factor-erythroid 2-related factor 2 (NRF2), as well as the transcription of downstream target genes, including nicotinamide adenine dinucleotide phosphate quinone dehydrogenase 1 and heme oxygenase-1 (P<0.05). Additionally, serum and hepatic GSH and SOD levels increased following liraglutide therapy (P<0.05). Hence, it was proposed that liraglutide may enhance the antioxidant activity of liver cells by activating the NRF2 signaling pathway, thereby reducing liver cell apoptosis induced by glucolipotoxicity in ZDF rats, which may shed light on the application of liraglutide in the treatment of diabetes- and obesity-induced liver injury.